Awareness and Practice of Contraception in Child Bearing Age Women - Kinza Alam; Aisha Yousaf; Noureen Yousaf; Inam Qadir; Foqia Taseer Hunana (Journal of Rawalpindi Medical College, 2018)
Background: To assess the awareness and usage of various methods of family planning among the child bearing age married women . Methods: In this cross sectional study married females (n=524) between 15-45 years of age were selected .Information was obtained regarding knowledge and pattern of utilizing family planning (FP) services. The source of knowledge either from media, family members or friends was noted. Information regarding contraceptive methods like natural, barrier, pills, injectable hormones, intrauterine contraceptive device (IUCD), or permanent method like vasectomy and tubal ligation was assessed. The reason for selection of the contraceptive method was asked. The reason for nonpractice FP was also asked. Results Mean age of the female was 34.12±7.43 years. Majority (89%) of the women had awareness about contraception and is practised by 51%.. Barrier method was the most practiced (37.8%) followed by pills (18%) and intra-uterine contraceptive device (17%). Health professionals were the major source of information (64%) while media had least role (7%). About 43% were those who never used any contraceptive method and those who stopped method later was due to husband disagreement (33%) or due to fear of side effects (>29%). Conclusion. Despite having knowledge, there is a wide gap between awareness and practice of contraception. One of the major factors among reasons of non-use of contraception is husband disagreement and fear of side effects. Role of media should be encouraged by government to increase the practice of contraception.